2002
DOI: 10.1172/jci200213229
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of prostasin by aldosterone in the kidney

Abstract: Prostasin is a serine protease present in mammalian urine that increases the activity of the epithelial sodium channel (ENaC) when the two are coexpressed in Xenopus oocytes. To determine if aldosterone, one of the principal regulators of urinary Na reabsorption by the distal nephron, affects prostasin expression, we examined prostasin mRNA and protein in a cultured mouse cortical collecting duct cell line (M-1), whole rats, and patients with primary aldosteronism. Aldosterone treatment of M-1 cells substantia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 18 publications
1
14
1
Order By: Relevance
“…Initial clinical studies indicated that urinary prostasin is elevated in patients with hyperaldosteronism [48]. Recent clinical studies have suggested more generally that urinary prostasin may serve as an in vivo marker of activation of ENaC [49], correlate with urinary aldosterone [50], and increase with pressure natriuresis [51].…”
Section: In Vivo Evidence Of Proteolytic Cleavage Of Enac Subunitsmentioning
confidence: 99%
“…Initial clinical studies indicated that urinary prostasin is elevated in patients with hyperaldosteronism [48]. Recent clinical studies have suggested more generally that urinary prostasin may serve as an in vivo marker of activation of ENaC [49], correlate with urinary aldosterone [50], and increase with pressure natriuresis [51].…”
Section: In Vivo Evidence Of Proteolytic Cleavage Of Enac Subunitsmentioning
confidence: 99%
“…Prostasin/CAP-1 stimulates the activity of ENaC when they are coexpressed in Xenopus oocytes [6][7][8]. In addition, we showed that aldosterone increases the expression of prostasin in both in vitro and in vivo conditions [9]. These results indicate that prostasin is an important physiologic regulator of sodium reabsorption in the kidney through EnaC, and suggest the possibility that prostasin is involved in the development of salt-sensitive hypertension.…”
mentioning
confidence: 68%
“…The resulting antisera were affinity-purified against the immunizing peptide. The specificity of the antibody was evaluated by comparing the blots with previously reported antibody [9,19].…”
Section: Antibody Generationmentioning
confidence: 99%
See 2 more Smart Citations